Plant life in campo rupestre: New lessons from an ancient biodiversity hotspot - Morellato, L. Patrícia C. [UNESP]; Silveira, Fernando A.O. (Elsevier, 2018)
The years 2011–2020 represent the United Nations Decade of Biodiversity, aiming to inspire worldwide actions to support biodiversity conservation. This Special Issue illustrates the current knowledge of plant life in campo rupestre, a megadiverse, highly-endemic vegetation complex, and one under alarming and unprecedented threats. The major research areas grouping the 27 contributions to the Special Issue are: i) plant diversity, ii) species coexistence, regeneration niche and climate change, iii) ecology of species interactions, iv) plant life on canga, and v) fire, regeneration ecology, and conservation. We highlight knowledge gaps in plant life in campo rupestre and suggest priority avenues of future research and steps forward to understand and preserve ancient ecosystems worldwide. Such efforts include the need to: 1) better assess the ecology of herbaceous species, 2) understand the effects of global change drivers on the vulnerability of endemic species, 3) understand how plant functional diversity and plant–animal interactions shape community structure and function, 4) apply new technologies (cameras, drones and remote sensing proxies) to understand plant phenology in space and time, 5) unravel diversification patterns and distinguish paleoendemism from neoendemism, 6) to disentangle the ecological and evolutionary role of fire, 7) gain insight into the factors that limit ecological restoration in degraded campo rupestre, 8) increase awareness and value of ecosystem services, 9) identify essential variables, key measures and areas to conserve campo rupestre, 10) promote reviews and research comparing old ecosystems. Therefore, burgeoning literature on campo rupestre will benefit from long-term multi- and trans-disciplinary research investigating a wide array of topics, from plant ecology to ecosystem functioning to biodiversity conservation and ecological restoration. All knowledge must reach stakeholders, and it should be translated into an ecosystem services assessment for guiding the rational stewardship of campo rupestre and for benefiting local people. A key step forward in the understanding of plant life in campo rupestre is the OCBIL Theory (old, climatically-buffered, infertile landscapes), which provides a theoretical framework of testable hypotheses and cross-continental comparisons. We anticipate this Special Issue will foster collaborative research leading to a deeper understanding and appreciation of one of the world's most ancient ecosystems.
Keywords: Endemism; Inselbergs; Megadiverse ecosystems; OCBIL theory; Rocky outcrops; Rupestrian grasslands; Tropical mountaintop grasslands